Finance and Development, December 2003. (Finance and Development; Finance and Development ;, 2003)
This paper describes why the international community needs to act now to stand a chance of meeting the Millennium Development Goals (MDGs). The paper gives example of Ethiopia, one of the poorest countries in the world, with an estimated per capita income of about USD 100. According to the World Bank, recent national household surveys find 44 percent of the people in Ethiopia cannot meet basic needs. The paper discusses that Ethiopia in many ways epitomizes why the MDGs are important and why more money is needed to achieve them.